PELAKSANAAN PELATIHAN BAHASA INGGRIS DALAM PROGRAM PENDIDIKAN KECAKAPAN KERJA (PKK) - Resti Anggraini; Ilham Abdullah; Ririn Gusti (UNIB Press, Universitas Bengkulu, 2020)
The purpose of this study is to determine the implementation of English competency tests in work skills education programs at LKP Cororado English Course Bengkulu City. This research is a qualitative research with as many as three research subjects and data collection techniques using interview, observation and documentation techniques. While data analysis techniques include data reduction, data presentation, and drawing conclusions. Checking the validity of the data using triangulation ranging from time triangulation, subject triangulation and technique triangulation. The results showed that the implementation of the competency test went well and in accordance with existing procedures, had adequate supporting facilities and facilities. However, the number of competency test participants who get incompetent results is due to several factors, namely the training carried out does not refer to graduate competency standards, design of learning implementation and syllabus. The training method only studies examples of existing problems. In addition, the training schedule is too tight and does not reach the minimum number of training hours, which is 144 hours. Keywords: Implementation, Competency Test, English